Načelo absolutnih prednosti - Cepec, Jaka (Pravnik, 2025)
The absolute priority rule is a fundamental rule of corporate bankruptcy law providing that, in the event of a bankruptcy proceeding, all creditors must be paid in full before equity holders retain any position in the reorganised debtor or are entitled to any payment in liquidation. The rule also requires that all senior creditors be paid in full before junior creditors can collect on outstanding debts. This rule was first noted by Bonbright and Bergeman in 1928. In liquidation cases, the role of the rule is internationally undisputed as an effective and perfectly logical one, and there are no dilemmas regarding its application. The rule simply restates the idea of a stratified ownership structure in which one has bargained to be paid before others. On the other hand, the case for the absolute priority rule in reorganisation proceedings is not as clear or strong. There has been an extensive law and economics debate on the subject, but there is still considerable disagreement as to whether potential exceptions to the absolute priority rule could be justified on the basis of economic efficiency. The author attempts to add to the already abundant literature on the absolute priority rule by adding insights from Slovenian legislation and presenting empirical insights from Slovenian cases.